Efektivitas Model Collaborative Learning terhadap Keterampilan Menulis Siswa dalam Pembelajaran Bahasa Indonesia: Kajian Systematic Literature Review - Rika Berliana Dabukke; Rima Melati; Rts Nurmarliawati; Helty; Liza Septa Wilyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Writing skills are a complex competency that often becomes an obstacle for students in learning Indonesian. This study aims to analyze the effectiveness of the Collaborative Learning model on students' writing skills through a Systematic Literature Review (SLR) approach. Based on the PRISMA guidelines, 9 scientific articles were obtained from the Google Scholar, Garuda, and DOAJ databases in the 2019–2025 period that met the inclusion criteria. The synthesis results show that the Collaborative Learning model is consistently effective in improving students' writing skills at various levels of education, both in terms of idea development, writing organization, and the use of linguistic rules. The main supporting factors for the success of this model include active discussion, exchange of ideas, and peer feedback. However, challenges such as inequality in group participation and time constraints need to be anticipated through optimal classroom management by teachers.